xy+3=w+15z

Simple and best practice solution for xy+3=w+15z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for xy+3=w+15z equation:


Simplifying
xy + 3 = w + 15z

Reorder the terms:
3 + xy = w + 15z

Solving
3 + xy = w + 15z

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + xy = w + -3 + 15z

Combine like terms: 3 + -3 = 0
0 + xy = w + -3 + 15z
xy = w + -3 + 15z

Reorder the terms:
xy = -3 + w + 15z

Divide each side by 'y'.
x = -3y-1 + wy-1 + 15y-1z

Simplifying
x = -3y-1 + wy-1 + 15y-1z

Reorder the terms:
x = wy-1 + -3y-1 + 15y-1z

See similar equations:

| 3+a=4a | | 6y+7+3y=3(3y-2)+13 | | 7x+7=4x-20 | | (8x-8)2-25=0 | | 6y+7+3y=3 | | x-5+x+.75x+.25x+3=360 | | 3t+7=-2t+27 | | y=-.5(4)-3 | | 6+-5x=-30 | | 16x+7=15+15x | | x-5+x+.75x+.25x+3=180 | | 7-4x-4(x-2)=-1 | | 9-2(x+3)=3 | | (98)x=6272 | | 2x-27=-15 | | 1.75c=7.5 | | 13y+19=6(9+1y)+18 | | y=-.5(2)-3 | | x^2-28x=-49 | | x+102=4*x | | 4-2(5-2x)=9-6x | | m^3-4m^2+5m-1=0 | | y=-.5(-2)-3 | | 3n/5=-20 | | 6+12x=112+3x+2 | | y=-.5(-4)-3 | | B+10=-5 | | 3.7y(-4.5y)(-0.1y)= | | 65y=4(16y+110) | | 7-13x-5-8x=5 | | -1+f/2=-1 | | 20-n=40 |

Equations solver categories